2005
DOI: 10.1093/aje/kwi248
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nonsteroidal Antiinflammatory Drugs and Risk of Colon Cancer in a Population-based, Case-Control Study of African Americans and Whites

Abstract: African Americans have the highest colon cancer incidence and mortality rates among all US ethnic groups. Epidemiologic studies suggest that use of nonsteroidal antiinflammatory drugs (NSAIDs) is associated with a reduced risk of colon cancer, but no study to date with adequate sample size has reported on the association among African Americans. The authors examined the association between NSAID use and risk of colon cancer in a population-based, case-control study in North Carolina that enrolled 731 African-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 53 publications
2
32
0
1
Order By: Relevance
“…High intake of beta carotene, vitamin C and calcium are associated with a lower risk of colorectal cancer in the white population whereas high intake of vitamin C and E are inversely associated with colorectal cancer risk in the African-American population [54] . Usage of non-steroidal anti-inflammatory drugs is associated with a reduced risk of colorectal cancer and this association did not vary among African Americans and Whites [55] . Fiber consumption is significantly associated with 50%-60% reduced risk of colorectal cancer in African Americans and non-significantly with 30% reduced risk of colorectal cancer in Whites [56] .…”
Section: Racial Variation Of Colorectal Cancer Riskmentioning
confidence: 84%
“…High intake of beta carotene, vitamin C and calcium are associated with a lower risk of colorectal cancer in the white population whereas high intake of vitamin C and E are inversely associated with colorectal cancer risk in the African-American population [54] . Usage of non-steroidal anti-inflammatory drugs is associated with a reduced risk of colorectal cancer and this association did not vary among African Americans and Whites [55] . Fiber consumption is significantly associated with 50%-60% reduced risk of colorectal cancer in African Americans and non-significantly with 30% reduced risk of colorectal cancer in Whites [56] .…”
Section: Racial Variation Of Colorectal Cancer Riskmentioning
confidence: 84%
“…In a secondary analysis of data from the Aspirin/ Folate Polyp Prevention Study, Kim et al examined risk of recurrent adenomas among subjects-randomized to either 81 mg aspirin or 325 mg aspirin daily versus placebowithin the WHO categories of BMI [5,27]. For advanced adenomas, the risk ratio of 325 mg aspirin compared with placebo was 1.23 (95% CI, 0.55-2.77) among normalweight subjects (BMI \ 25), 0.94 (95% CI, 0.54-1.64) among overweight (BMI [25][26][27][28][29], and 0.44 (95% CI, 0.17-1.10) among obese (BMI C 30). No clear pattern with BMI was observed for 81 mg aspirin or for adenoma overall.…”
Section: Discussionmentioning
confidence: 99%
“…Most observational epidemiological studies also point to a long latency for the effect of aspirin or non-aspirin NSAIDs (NA-NSAIDs) on CRC [16][17][18][19][20][21][22], but some studies have suggested that a protective effect may be achieved within a few years [23][24][25][26]. A recent post-trial analysis has suggested that the chemopreventive effect of NSAIDs on colorectal neoplasia may vary by body mass index (BMI) as marker for obesity [27]; however, the epidemiologic data on the influence of BMI are conflicting [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since this study did not provide risk estimates for users vs. nonusers, it was not included in the pooled estimates. A case-control study from North Carolina [27], including 294 African-American and 349 White colon cancer cases, gave a RR of 0.47 (95% CI: 0.27-0.80) for aspirin use, and similar risk estimates for use of any NSAIDs (RR = 0.49) and of non-aspirin NSAIDs only (RR = 0.46).…”
Section: Colon and Rectal Cancermentioning
confidence: 93%